2008
DOI: 10.1007/s11064-007-9416-8
|View full text |Cite
|
Sign up to set email alerts
|

Underlying Mechanism of Quercetin-induced Cell Death in Human Glioma Cells

Abstract: There has been considerable interest in recent years in the anti-tumor activities of flavonoids. Quercetin, a ubiquitous bioactive flavonoid, can inhibit proliferation and induce apoptosis in a variety of cancer cells. However, the precise molecular mechanism by which quercetin induces apoptosis in cancer cells is poorly understood. The present study was undertaken to examine the effect of quercetin on cell viability and to determine its underlying mechanism in human glioma cells. Quercetin resulted in loss of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 51 publications
4
49
0
Order By: Relevance
“…This effect might be linked to strong inhibition of topo II by both compounds [18,42]. The decrease in therapeutic dose of DB may prove important due to the chance for prevention of negative side effects induced by the drug, assuming that Q acts selectively: it inhibits proliferation only in neoplastic cells in parallel protecting normal tissues [13,21,36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This effect might be linked to strong inhibition of topo II by both compounds [18,42]. The decrease in therapeutic dose of DB may prove important due to the chance for prevention of negative side effects induced by the drug, assuming that Q acts selectively: it inhibits proliferation only in neoplastic cells in parallel protecting normal tissues [13,21,36].…”
Section: Discussionmentioning
confidence: 99%
“…Q affects directly various type kinases, e.g., protein kinase C, PI 3K, MAPK, ERK, CDK and their respective metabolic pathways, which play a significant role in carcinogenesis [16][17][18][19][20][21]. The studies on effects of carcinogens on normal cells in presence of Q, demonstrated also its antioxidant properties and a protective role against mutagenesis in healthy tissues [2,[22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Other researchers have also confirmed the observation that quercetin might have antiglioma activity. Kim et al found that quercetin induced cell death in human glioma cells (Kim, Choi et al, 2008). Mechanistically, they found that quercetin inhibited the ERK and Akt pathway and that ectopic expression of constitutively active forms of ERK and Akt protected against quercetin mediated cell death in glioma (Kim, Choi et al, 2008).…”
Section: Polyphenols As a Novel Treatment Options For Gliomasmentioning
confidence: 99%
“…Kim et al found that quercetin induced cell death in human glioma cells (Kim, Choi et al, 2008). Mechanistically, they found that quercetin inhibited the ERK and Akt pathway and that ectopic expression of constitutively active forms of ERK and Akt protected against quercetin mediated cell death in glioma (Kim, Choi et al, 2008). Furthermore, the inhibitor of apoptosis protein, survivin, was suppressed in a concentration dependent manner by quercetin (Kim, Choi et al, 2008).…”
Section: Polyphenols As a Novel Treatment Options For Gliomasmentioning
confidence: 99%
See 1 more Smart Citation